2017
DOI: 10.1515/ap-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Snail species diversity impacts the infection patterns of Echinostoma spp.: Examples from field collected data

Abstract: Rapid losses of biodiversity due to the changing landscape have spurred increased interest in the role of species diversity and disease risk. A leading hypothesis for the importance of biodiversity in disease reduction is the dilution effect, which suggests that increasing species diversity within a system decreases the risk of disease among the organisms inhabiting it. The role of species diversity in trematode infection was investigated using field studies from sites across the U.S. to examine the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Similar 'identity effects' for particular species in diluting infection among focal hosts has also been demonstrated for other disease systems (e.g. [49]). Debate surrounding the dilution effect hypothesis has often centred around whether observed changes in infection levels stem from shifts in host diversity or in host species composition.…”
Section: Discussionsupporting
confidence: 65%
“…Similar 'identity effects' for particular species in diluting infection among focal hosts has also been demonstrated for other disease systems (e.g. [49]). Debate surrounding the dilution effect hypothesis has often centred around whether observed changes in infection levels stem from shifts in host diversity or in host species composition.…”
Section: Discussionsupporting
confidence: 65%
“…Both species of herbivore represented in our experiment are known to to be important in nitrogen cycling and likely both raise nitrogen concentrations (e.g., Paterson et al, 2002 ; Mulholland et al, 1991 ; Griffiths & Hill, 2014 ). Although the experimental snail populations may appear small, 1–3 snail per 1L of water represents a high density ( Zimmermann, Luth & Esch, 2017 ). Thus, the effect of snails on nutrients may be consistent with expectations based on natural systems ( Hall Jr, Tank & Dybdahl, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have argued that the relationships species richness (i.e., the number of host species) and disease levels in a focal host are likely to be context dependent (LoGiudice et al, 2008; Randolph and Dobson, 2012; Rohr et al, 2020; Halliday et al, 2020). Previous empirical studies (Telfer et al, 2005; Dizney and Ruedas, 2009; Searle et al, 2016; Levine et al, 2017; Hydeman et al, 2017; Zimmermann et al, 2017; Luis et al, 2018) and theoretical studies (Dobson, 2004; Rudolf and Antonovics, 2005; Joseph et al, 2013; Mihaljevic et al, 2014; O’Regan et al, 2015; Searle et al, 2016; Faust et al, 2017; Roberts and Heesterbeek, 2018; Cortez and Duffy, 2021; Cortez, 2021) have shown that whether the addition of a host species leads to increased or decreased disease in a focal host depends on the specific characteristics (e.g., competitive ability or disease competence) of the host species that are present in the community and added to the community. The time varying signs and magnitudes of the global sensitivities in this study suggest that the context dependent relationships may also depend on the time scale of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Many empirical studies have shown that the absence or presence of a second host species can increase or decrease levels of disease in a focal host species (Telfer et al, 2005; Dizney and Ruedas, 2009; Searle et al, 2016; Levine et al, 2017; Hydeman et al, 2017; Zimmermann et al, 2017; Luis et al, 2018). This empirical work is complemented by modeling studies exploring how specific processes shape disease dynamics in two-host communities (Rudolf and Antonovics, 2005; O’Regan et al, 2015; Searle et al, 2016; Roberts and Heesterbeek, 2018; Cortez and Duffy, 2021).…”
Section: Introductionmentioning
confidence: 99%